Traffic pollution and the incidence of cardiorespiratory outcomes in an adult cohort in London. Issue 12 (24th June 2016) - Carey, I M; Anderson, H R; Atkinson, R W; Beevers, S; Cook, D G; Dajnak, D; Gulliver, J; Kelly, F J
Abstract : Objectives: The epidemiological evidence for adverse health effects of long-term exposure to air and noise pollution from traffic is not coherent. Further, the relative roles of background versus near traffic pollution concentrations in this process are unclear. We investigated relationships between modelled concentrations of air and noise pollution from traffic and incident cardiorespiratory disease in London. Methods: Among 211 016 adults aged 40–79 years registered in 75 Greater London practices between 2005 and 2011, the first diagnosis for a range of cardiovascular and respiratory outcomes were identified from primary care and hospital records. Annual baseline concentrations for nitrogen oxide (NOx ), particulate matter with a median aerodynamic diameter <2.5 μm (PM2.5 ) attributable to exhaust and non-exhaust sources, traffic intensity and noise were estimated at 20 m 2 resolution from dispersion models, linked to clinical data via residential postcode. HRs were adjusted for confounders including smoking and area deprivation. Results: The largest observed associations were between traffic-related air pollution and heart failure (HR=1.10 for 20 μg/m 3 change in NOx, 95% CI 1.01 to 1.21). However, no other outcomes were consistently associated with any of the pollution indicators, including noise. The greater variations in modelled air pollution from traffic between practices, versus within, hampered meaningful fine spatial scale analyses. Conclusions: The associations observed with heart failure may suggest exacerbatory effects rather than underlying chronic disease. However, the overall failure to observe wider associations with traffic pollution may reflect that exposure estimates based on residence inadequately represent the relevant pattern of personal exposure, and future studies must address this issue.